The Role of Posters in Promoting Awareness of the Federal Integrity Commission in Iraq - Ibrahim, Raghad AbdulSattar; Alshegeri, Sihaam Hassn (ALBAHITH ALALAMI, 2024)
This research examines the communicative processes of the Federal Integrity Commission, through which ideas, information, and experiences are conveyed to audiences. These processes take on various contexts and dimensions, utilizing straightforward and clear methods such as visual or written symbols. These activities often involve elements of influence and appeal, incorporating fundamental characteristics like beauty, effectiveness, and clarity to foster participation and convey meanings for a better understanding of communication. Using a survey methodology, the study analyzed a total of 51 posters produced by the Federal Integrity Commission between 2019 and 2022. These posters were displayed in government ministries, institutions, and public spaces. Content analysis of the posters revealed several key findings: 1- Communicators relied on indirect symbolic messaging to convey their media messages. 2- The posters predominantly employed "emotional appeals," which proved highly effective in engaging audiences. 3- "Awareness" emerged as the primary communicative function of the symbols in the posters, followed by "education," "deterrence," and "information," in descending order of frequency.